Diseño, Resistencia y Valores Estructurales de cerchas prefabricadas con Madera de Plantación - Moya-Roque, Róger; Tenorio-Monge, Carolina; Carranza-Solano, Mauricio; Saenz-Muñoz, Marta; Navarro-Mora, Ángel; Paniagua, Viviana (Instituto Tecnológico de Costa Rica. Vicerrectoría de Investigación y Extensión (VIE). Escuela de Ingeniería Forestal. Centro de Investigación en Innovación Forestal (CIF), 2016)
The objective of this research is design two pratt framing trusses for two span, 6 m and 9 m, and fabricated with Gmelina arborea and Hieronyma alchorneoides wood, using two types of fastener (nails and screws). As a complement to this objective: (i) it was evaluated different angles in the joints that can be used in the manufacture of trusses (ii) it was established the design values of these joint and trusses for using in small housing building, (iii) proposal of packing for these wood trusses, and (iv) presents construction and user manuals. Results showed that the maximum load values in the trusses and joint fabricated with H. alchorneoides wood were higher compared to the trusses fabricated with G. arborea wood. The design tables of the trusses for these two species of wood and two types of fastener (nails or screws) were proposed for span of 4 m, 5 m, 6 m and 7 m. The packing proposal proposed that two boxes of corrugated paperboard were packing the wood truss: one box with 2.5 m long will packing the largest pieces and second box with 1.6 m long will packing small boards. The manuals of assembly and users detail graphically how the trusses should be assembled and the conditions of use.
Informe Final de Proyecto de Investigación. Código del proyecto: 1401055
Keywords: Construcción liviana; Estructura; Madera; Especies tropicales; Empaque